Selection signatures associated with adaptation in South African Drakensberger, Tuli, and Nguni beef breeds. - Van Marle-Koster, Este (University of Pretoria, 2024)
Dissertation (MSc Agric (Animal Science: Animal Breeding and Genetics))--University of Pretoria, 2024.